(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article analyzes the ideological foundations of the dramatic works of Turgut Özakman and Abdurauf Fitrat, two prominent representatives of Turkish and Uzbek modern literature. Both playwrights reflected national awakening, social transformation, and the struggle for cultural and political independence in their dramas. Through a comparative literary analysis, this study examines themes such as national identity, reformism, resistance, and the role of intellectuals in society. The findings demonstrate that although Özakman and Fitrat emerged from different historical contexts, their dramatic works share common ideological concerns rooted in national revival and modernization. At the same time, differences in stylistic expression and historical circumstances shape their distinct dramatic visions.